Anisotropic behavior of hydrogen in the formation of pentagonal graphene domains. (August 2015) - Jung, Da Hee; Kang, Cheong; Yoon, Duhee; Cheong, Hyeonsik; Lee, Jin Seok
Abstract: Variously shaped graphene domains are of significant interest since the electronic properties of pristine graphene are strongly dependent on its size, shape, and edge structures. With the consideration that the reactivity of graphene is governable by the p -electron structure at its edge, a number of attempts have been made to grow variously shaped graphene domains and to define their edge structures. In this work, we explored the anisotropic behavior of hydrogen in the formation of graphene domains during atmospheric pressure chemical vapor deposition. As increasing the hydrogen or reducing the methane partial pressure, the formation of pentagonal graphene domains was accelerated through anisotropic growth and etching. Their edge structures were characterized using polarization-dependent D and G peak Raman spectroscopy. This work contributes significantly to improving graphene-based engineering by allowing graphene shapes and domain edges to be tuned, and also provides greater insight into the electronic properties of graphene devices.